2009
DOI: 10.3324/haematol.13601
|View full text |Cite
|
Sign up to set email alerts
|

Detection of paroxysmal nocturnal hemoglobinuria clones in patients with myelodysplastic syndromes and related bone marrow diseases, with emphasis on diagnostic pitfalls and caveats

Abstract: BackgroundThe presence of paroxysmal nocturnal hemoglobinuria clones in the setting of aplastic anemia or myelodysplastic syndrome has been shown to have prognostic and therapeutic implications. However, the status of paroxysmal nocturnal hemoglobinuria clones in various categories of myelodysplastic syndrome and in other bone marrow disorders is not well-studied. Design and MethodsBy using multiparameter flow cytometry immunophenotypic analysis with antibodies specific for four glycosylphosphatidylinositol-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 30 publications
8
82
1
2
Order By: Relevance
“…19,20,22,23 The association between PNH and MDS appears to be confined to low-risk categories of MDS, particularly the refractory anemia (RA) variant. [18][19][20]22 Using high-sensitivity flow cytometry in which Ն 0.003% of GPI-AP-deficient RBCs or peripheral mononuclear cells was classified as abnormal, Wang et al reported that 21 of 119 (18%) patients with RA MDS had a population of PNH cells, whereas GPI-AP-deficient cells were not detected in patients with RA with ringed sideroblasts, RA with excess of blasts, or RA with excess of blasts in transformation.…”
Section: Subclinical Pnhmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20,22,23 The association between PNH and MDS appears to be confined to low-risk categories of MDS, particularly the refractory anemia (RA) variant. [18][19][20]22 Using high-sensitivity flow cytometry in which Ն 0.003% of GPI-AP-deficient RBCs or peripheral mononuclear cells was classified as abnormal, Wang et al reported that 21 of 119 (18%) patients with RA MDS had a population of PNH cells, whereas GPI-AP-deficient cells were not detected in patients with RA with ringed sideroblasts, RA with excess of blasts, or RA with excess of blasts in transformation.…”
Section: Subclinical Pnhmentioning
confidence: 99%
“…19,20,22,23 The association between PNH and MDS appears to be confined to low-risk categories of MDS, particularly the refractory anemia (RA) variant. [18][19][20]22 Using high-sensitivity flow cytometry in which Ն 0.003% of GPI-AP-deficient RBCs or peripheral mononuclear cells was classified as abnormal, Wang et al reported that 21 of 119 (18%) patients with RA MDS had a population of PNH cells, whereas GPI-AP-deficient cells were not detected in patients with RA with ringed sideroblasts, RA with excess of blasts, or RA with excess of blasts in transformation. 20 Compared with patients with RA without a population of PNH cells, RA patients with a population of PNH cells had a distinct clinical profile characterized by the following features: (1) less pronounced morphological abnormalities of the blood cells, (2) more severe thrombocytopenia, (3) a lower rate of karyotypic abnormalities, (4) a higher incidence of HLA-DR15, (5) a lower rate of progression to acute leukemia, and (6) a higher probability of response to cyclosporine therapy.…”
Section: Subclinical Pnhmentioning
confidence: 99%
See 1 more Smart Citation
“…PNH clones can be detected in the setting of MDS, and their presence may not be related to the pre-leukemic nature of MDS but rather linked to BM failure, similar to aplastic anemia [22]. Furthermore, PNH can represent the clinical evolution of another BM disorder, and especially of MDS cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by a mutation in the phosphatidyl inositol glycan-class A gene leading to partial or complete loss of the cell membrane molecule called glycosyl phosphatidyl inositol (GPI) (15,16 (14), data analysis has not been standardized. The majority of current analytical methods use manual gating to enumerate PNH cells (14)(15)(16)(17)(18)(19) although new automated analysis techniques that improve the objectivity of operator input have also been recently developed (19). Gating strategies imply the recognition of the various cell types (monocytes, neutrophil granulocytes, and red blood cells) based on the expression of various phenotypic markers.…”
Section: Flow Cytometric Testing Of Immunological Markers For Gating mentioning
confidence: 99%